Preexposure to one social threat alters responses to another social threat: Behavioral and electrophysiological evidence. - Fang, Xu; Kerschreiter, Rudolf; Yang, Yu-Fang; Niedeggen, Michael (Cognitive, Affective & Behavioral Neuroscience, 2024)
A recent Cyberball study has indicated that the experience of loss of control can affect how people process subsequent social exclusion. This "preexposure effect" supports the idea of a common cognitive system involved in the processing of different types of social threats. To test the validity of this assumption in the current study, we reversed the sequence of the preexposure setup. We measured the effects of social exclusion on the subsequent processing of loss of control utilizing event-related brain potentials (ERPs) and self-reports. In the control group (CG, n = 26), the transition to loss of control elicited significant increases in both the P3 amplitude and the self-reported negative mood. Replicating the results of the previous preexposure study, these effects were significantly reduced by the preexposure to an independent social threat (here: social exclusion). In contrast to previous findings, these effects were not modulated by the discontinuation (EG1disc, n = 25) or continuation (EG2cont, n = 24) of the preexposure threat. Given that the P3 effect is related to the violation of subjective expectations, these results support the notion that preexposure to a specific social threat has widespread effects on the individuals' expectancy of upcoming social participation and control.